Analisis Kegagalan Manajemen Risiko: Studi Kasus Pada PT. Sri Rejeki Isman Tbk. (Sritex) - M. Ihsan Rangkuti (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to analyze the factors causing risk management failure at PT Sri Rejeki Isman Tbk (Sritex), an international textile company that went bankrupt in October 2024. As a public company that was once the pride of the national textile industry, Sritex's failure is an important precedent in the context of corporate risk governance in Indonesia. The method used in this research is a literature study with a qualitative-descriptive approach. Data was collected through literature searches, media reports, academic journals, policy documents, and publications of relevant state institutions. The results showed that risk management failure at Sritex occurred due to weak integrated risk management, which included strategic risk, financial risk, and operational risk. Strategic risk includes aggressive expansion decisions without analysis of global market uncertainty. Financial risk was characterized by the accumulation of foreign currency-denominated debt without a hedging strategy, which exacerbated liquidity pressures during the rupiah depreciation. Meanwhile, operational risk is evident in the absence of an emergency response system and the inability to maintain efficiency during the disruption of the COVID-19 pandemic. These observations are linked to modern risk management theories, including the COSO Enterprise Risk Management framework and the ISO 31000 standard, which emphasize the importance of systematic, proactive and adaptive risk management. This study makes a theoretical contribution to the understanding of risk management failures in publicly listed companies, and suggests the need for integration of risk policies in strategic and operational decision-making. This study also recommends the need for improved regulation and supervision of risk governance in public companies in Indonesia.